2006
DOI: 10.1096/fj.06-5806fje
|View full text |Cite
|
Sign up to set email alerts
|

H. influenzae potentiates airway epithelial cell responses to rhinovirus by increasing ICAM‐1 and TLR3 expression

Abstract: Rhinovirus (RV) is an important trigger of chronic obstructive pulmonary disease (COPD) exacerbations. In addition, respiratory viruses are more likely to be isolated in patients with a history of frequent exacerbations, suggesting that these patients are more susceptible to viral infection. To examine potential mechanisms for cooperative effects between bacterial and viral infection in COPD, we studied the responses of cultured human airway epithelial cells to nontypeable Hemophilus influenzae and RV. In both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
124
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 45 publications
8
124
2
2
Order By: Relevance
“…Presented data are representative for two independent experiments. *p , 0.05, **p , 0.01. evidence that TLR3 is also involved in antibacterial responses (13,14). Beyond that, upon activation, TLR3 induces the same TRIFdependent signaling events as endosomal TLR4, resulting in activation of the MyD88-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presented data are representative for two independent experiments. *p , 0.05, **p , 0.01. evidence that TLR3 is also involved in antibacterial responses (13,14). Beyond that, upon activation, TLR3 induces the same TRIFdependent signaling events as endosomal TLR4, resulting in activation of the MyD88-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that TLR3 may also be associated with bacterial infection. Sajjan et al (13) have reported that TLR3 expression is upregulated in airway epithelial cells during infection with nontypeable Haemophilus influenzae (NTHi), resulting in enhanced rhinovirus-induced chemokine release. In addition, NTHi is capable of directly activating TLR3 (14).…”
mentioning
confidence: 99%
“…The other second hypothesis claims that virus infections of the respiratory tract imbalance the respiratory microbial community7, 8 and thus predispose to bacterial superinfections2, 8, 9, 10: Longitudinal studies have revealed a clear and positive association between viral and bacterial infections of the airway as acute otitis media, sinusitis, purulent nasopharyngitis, acute bronchitis, tonsillitis and pneumonia all often occur after local viral infection 2, 5, 7. Interactions between viruses and bacteria in the pathogenesis of respiratory infections have been investigated by others applying techniques used in microbiology and molecular biology1, 2, 7, 8, 9: The mechanisms by which viruses influence bacterial colonisation and invasion are diverse and include disruption of the epithelium barrier, upregulation of adhesion proteins, production of viral factors and dysfunction of immune system components 1, 2, 7, 9…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between viruses and bacteria in the pathogenesis of respiratory infections have been investigated by others applying techniques used in microbiology and molecular biology1, 2, 7, 8, 9: The mechanisms by which viruses influence bacterial colonisation and invasion are diverse and include disruption of the epithelium barrier, upregulation of adhesion proteins, production of viral factors and dysfunction of immune system components 1, 2, 7, 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation